144k views
2 votes
Simplify the expressions 4y+2x-y+8​

2 Answers

1 vote

Answer:

3y+2x+8

Explanation:

All you really do is combine the like terms, which in this case is the 3y and the -y. think of the y more as -1y and that is why it's subtrcated.

User Junejo
by
5.1k points
3 votes

Hey there!

4y + 2x - y + 8

= 4y + 2x - 1y + 8

COMBINE the LIKE TERMS

= (4y - 1y + (2x) + (8)

= (4y - y) + (2x) + (8)

= (2x) + (4y - y) + 8

= 2x + 3y + 8

Therefore, your answer is: 2x + 3y + 8

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

User Poncho
by
4.6k points